The association between VEGF genetic variations and the risk of bronchopulmonary dysplasia in premature infants: a meta-analysis and systematic review - Golshan-Tafti, Mohammad; Bahrami, Reza; Dastgheib, Seyed Alireza; Hosein Lookzadeh, Mohamad; Mirjalili, Seyed Reza; Yeganegi, Maryam; Aghasipour, Maryam; Shiri, Amirmasoud; Masoudi, Ali; Shahbazi, Amirhossein; Azizi, Sepideh; Noorishadkam, Mahmood; et al. (Frontiers in Pediatrics, 2024)
Objective Previous studies on the link between VEGF gene polymorphisms and bronchopulmonary dysplasia (BPD) have yielded inconsistent results. This meta-analysis sought to clarify the relationship between genetic variations in the VEGF gene and the risk of BPD. Methods Data were collected from multiple databases, including PubMed, Scopus, EMBASE, and CNKI, up to January 5, 2024. Results Nineteen case-control studies were analyzed, featuring 1,051 BPD cases and 1,726 healthy neonates. The analysis included four studies on the −460T/C polymorphism (312 cases, 536 controls), four on the −2578C/A polymorphism (155 cases, 279 controls), six on the +405G/C polymorphism (329 cases, 385 controls), and five on the +936C/T polymorphism (225 cases, 526 controls). The meta-analysis suggests that the −460T/C polymorphism may protect against BPD (C vs. T: OR =<sans-serif> 0</sans-serif>.715, 95% CI 0.543–0.941, p = 0.017; CC vs. TT: OR =<sans-serif> 0</sans-serif>.478, 95% CI 0.233–0.983, p = 0.045; CC vs. CT + TT: OR =<sans-serif> 0</sans-serif>.435, 95% CI 0.248–0.764, p = 0.004). No significant associations were found between the −2578C/A, +405G/C, and +936C/T polymorphisms and BPD susceptibility. Conclusions This meta-analysis indicates that the C allele of the −460T/C polymorphism may offer protection against BPD. No significant associations were observed for the −2578C/A, +405G/C, and +936C/T polymorphisms.